Capital social y desarrollo económico local : posibilidades y límites de OVOP en Colombia (2017)
OVOP Colombia is an alternative to promote local development based on particular products or services of the territories. However, in a fragmented society such as Colombia, the project faces important challenges to promote the construction of social capital and achieve economic and social transformations in the territory. Starting from a governance approach, the paper analyzes whether OVOP fosters the construction of social capital within Colombian communities based on the study of three specific variables: associativity, leadership and conflict management. Based on focused initiatives, the analysis identifies for each scenario: 1) positive tools and results that foster trust and strengthen associativity in Mompox (Bolivar); 2) absence of effective mechanisms to move to a collective leadership in Susa (Cundinamarca) and 3) concertation spaces without overcoming divisions within the community in Guamo (Tolima). The analysis results in a series of recommendations to promote the articulation between local actors within Colombian communities as one of the determinants of the success and sustainability of the project.